Synbranchus doeringii Weyenbergh, 1877, a justified emendation of S. döringii (Pisces: Synbranchidae) - Koerber, Stefan (Zootaxa, 2007)
Weyenbergh in 1877 described Synbranchus döringii from lakes near Santa Fé, Argentina. Synbranchus döringii is considered as a synonym of Synbranchus marmoratus, a widespread species occurring throughout Central and South America (Kullander 2003). Synbranchus Döringii, as spelled in the original description, is frequently listed sub S. doringii by recent authors (e.g. Eschmeyer 1998; Kullander 2003). Eschmeyer emended Döringii to doringii and additionally said “Species name originally spelled as Döringii; if based on a German name the correct spelling would be doeringii”.